Soft Law, Solid Implementation? The Influence of Precision, Monitoring and Stakeholder Involvement on Norwegian Implementation of Arctic Council Recommendations - Soltvedt, Ida Folkestad (Arctic Review on Law and Politics, 2017)
The Arctic Council has been criticized for its lack of legal status and, consequently, the supposedly low level of implementation among member states. Studying Norwegian implementation of six Arctic Council recommendations, this article challenges that view. I start by assuming that international law is not binary, that soft law is not a uniform phenomenon, and that soft law recommendations may entail certain characteristics—precision, monitoring, and stakeholder involvement—that can enhance their implementation nationally. Additionally, malignancy—an important barrier to national implementation—is taken into account. The Norwegian authorities have implemented several of the recommendations studied, and the characteristics are found to have a bearing on the outcomes. However, the absence of malignancy stands out as the most significant condition for achieving national implementation. (Published: May 2017) Citation: Ida Folkestad Soltvedt. “Soft Law, Solid Implementation? The Influence of Precision, Monitoring and Stakeholder Involvement on Norwegian Implementation of Arctic Council Recommendations.” Arctic Review on Law and Politics, Vol. 8, 2017, pp. 73–94. http://dx.doi.org/10.23865/arctic.v8.639